ChemInform Abstract: Ring‐Rearrangement Metathesis of 7‐Azanorbornenes as an Entry to 1‐Azabicyclo[n.3.0]alkenones. Issue 45 (14th October 2013) - Rojas, Victor; Carreras, Javier; Avenoza, Alberto; Busto, Jesus H.; Peregrina, Jesus M.
Abstract This metathesis reaction of the title bornenes allows the construction of pyrrolizidine, indolizidine, and pyrrolo[1, 2‐α]azepine cores.